The cult of King Charles the martyr - Lacey, Andrew (Studies in modern British religious history, 2003)
The royal actor -- Habeas corpus : foundations of the cult before 1649 -- By the rivers of Babylon : the cult in exile -- In verbo tuo spes mea : fashioning the royal martyr -- The return to Zion : he cult and the restored monarchy -- Irreligious rants and civil seditions : the cult in 'the age of party' -- A pattern of religion and virtue : the conservative martyr -- Our own, our royal saint